PENDAMPINGAN LATIHAN FISIK DAN MENTAL SPIRITUAL PADA LANSIA DI DESA KEDUNGDAWA - Bunga Jannahtu Sholeha; Salis Apriliani; Ahmad Waridi; Siti Hindun; Duriyah (Al Naqdu, 2023)
Physical and mental exercise programs are programs carried out to improve the physical strength and health of the elderly. This program is carried out in line with the service of KKM IAI Cirebon. It is very important to pay attention to the health of the elderly, considering that the elderly group has different nutritional needs from other age groups. This is due to changes in body composition and decreased physical and mental activity, with increasing age, decreased energy requirements. The purpose of this study was to provide physical and mental training assistance to the elderly in the village of Kedungdawa. The methods used to achieve these goals are 1). Mentoring 2.) Education. The physical and mental training assistance was carried out on September 15, 2022 in yhe village of kedungdawa RW 01 which was attended by 15 elderly people, while the activities carried out were physical exercise assistance by inviting the elderly to walk, and mental assistance by talking about the past lives they had gone trough. During his life.